An acoustic study of the rhythm of fulfulde / Ahmadu Shehu - Shehu, Ahmadu (2014)
Fulfulde is a language widely spoken in West and Central African countries by people who call themselves Fulɓe, also known as Fulani in English. Considerable researche has been conducted on the phonology of the language, but there appears to be a dearth of research on rhythm, as none of the available literature discuss the rhythm of this language in any detail. This research is aimed at describing the acoustic correlates of the rhythm of Fulfulde in comparison with Nigerian English, and to provide the translated version of a phonetic text ‘North Wind and the Sun’ (IPA, 1999) which can serve henceforth as an instrument in the acoustic investigation of the language. Though this popular phonetic text has been in use for decades and has been translated into hundreds of languages, its Fulfulde version is so far not available. 10 speakers of Fulfulde and 10 speakers of Nigerian English were recorded. The normalized Pairwise Variability Index (Grabe & Low, 2002) and Varco V (Dellwo, 2006) values which are rhythmic indexes were used to measure the rhythm of the two languages. The findings show that the rhythm of Fulfulde is syllable-timed, but along the continuum, Fulfulde is more stress-timed than Nigerian English. The results raised further questions on the influence of native language on the rhythm of Nigerian English.